In-situ multispectral and bathymetric measurements over a supraglacial lake in western Greenland using a remotely controlled watercraft ... - Tedesco, Marco; Steiner, N. (Columbia University, 2011)
Supraglacial lakes form from meltwater on the Greenland ice sheet in topographic depressions on the surface, affecting both surface and sub-glacial processes. As the reflectance in the visible and near-infrared regions of a column of water is modulated by its height, retrieval techniques using spaceborne remote sensing data (e.g. Landsat, MODIS) have been proposed in the literature for the detection of lakes and estimation of their volume. These techniques require basic assumptions on the spectral properties of the water as well as the bottom of the lake, among other things. In this study, we report results obtained from the analysis of concurrent in-situ multi-spectral and depth measurements collected over a supraglacial lake during early July 2010 in West Greenland (Lake Olivia, 69°36'35" N, 49°29'40" W) and aim to assess some of the underlying hypotheses in remote sensing based bathymetric approaches. In particular, we focus our attention on the analysis of the lake bottom albedo and of the water ...